2021
DOI: 10.3390/en14041098
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Changes in the Energy Balance in EU Countries

Abstract: The main purpose of the paper was to present the energy balance in the EU countries. The specific objectives were to show the concentration and directions of changes in the demand, production, import, and export of energy in the EU countries, to determine the degree of variability (or stability) of these energy balance parameters, and to establish the correlation between the energy balance parameters and economic parameters. All members of the European Union were determinedly selected for research on 31 Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 96 publications
1
29
0
Order By: Relevance
“…For many years, energy and climate policy has been the priority area of activity for the EU, and in recent years, it has become increasingly important [77,78]. Currently undertaken activities are closely related to the European Green Deal and are part of the implementation of the objectives of Agenda 2030 (goals: 7 on "Clean and Accessible Energy" and 13 on "Climate Action"), adopted in 2015 by the UN General Assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, energy and climate policy has been the priority area of activity for the EU, and in recent years, it has become increasingly important [77,78]. Currently undertaken activities are closely related to the European Green Deal and are part of the implementation of the objectives of Agenda 2030 (goals: 7 on "Clean and Accessible Energy" and 13 on "Climate Action"), adopted in 2015 by the UN General Assembly.…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that very significant progress in sustainable development in the studied years was achieved by the Czech Republic, Germany, Estonia, Ireland, Lithuania, Hungary, Luxembourg, Malta, Poland, Slovakia, Romania, and Italy. These are countries, which have clearly reduced GHG emissions (both in total and from the energy sector), increased the share of RES in the energy mix [77], improved energy productivity, and reduced the level of energy poverty.…”
Section: Assessing Individual Eu27 Countries In Terms Of Theirmentioning
confidence: 99%
“…As a result, the profitability of the investment significantly decreased [60][61][62][63][64]. In turn, attracting investments in renewable energy is influenced by e.g., tax incentives and properly designed feed-in tariffs [65][66][67][68][69][70]. About 80% of countries with high and higher than medium level of development offer support for renewable energy investments [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the use of large volumes of energy reflects high levels of economic growth. There is a great number of research confirming such relationships [13][14][15][16][17][18][19][20][21][22][23][24][25]. Ozturk and Acaravci [26] presented the feedback between energy absorption and economic growth in Hungary.…”
Section: Introduction 1the Importance Of Transport In Energy Consumptionmentioning
confidence: 99%